2019
DOI: 10.1159/000499145
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Practices and Parenting: A Pathway to Child Health and Family Happiness

Abstract: Feeding and parenting are inextricably linked. The complex bidirectional interactions between parent feeding practices and child eating behaviour shape the early feeding environment which in turn interacts with genetic predispositions to lay the foundation for life-long eating habits and health outcomes. Parent feeding and child (and parent) eating are central to the fabric of family life and are strongly rooted in culture and tradition. Yet, many parents experience stress and anxiety related to this ubiquitou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(135 citation statements)
references
References 64 publications
5
123
0
7
Order By: Relevance
“…Moreover, this time is considered a sensitive period for establishing healthy dietary habits [ 2 ]. Breastfeeding, complementary feeding, parental feeding practices, but also social and family environment, play a crucial role in the development of children’s food preferences, attitudes, and dietary patterns [ 2 , 3 , 4 ]. However, children are evolutionarily predisposed to prefer high-energy, sweet and salty foods [ 2 , 5 ], as well as to reject bitter or new food items which may be extremely challenging for parents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this time is considered a sensitive period for establishing healthy dietary habits [ 2 ]. Breastfeeding, complementary feeding, parental feeding practices, but also social and family environment, play a crucial role in the development of children’s food preferences, attitudes, and dietary patterns [ 2 , 3 , 4 ]. However, children are evolutionarily predisposed to prefer high-energy, sweet and salty foods [ 2 , 5 ], as well as to reject bitter or new food items which may be extremely challenging for parents.…”
Section: Introductionmentioning
confidence: 99%
“…However, children are evolutionarily predisposed to prefer high-energy, sweet and salty foods [ 2 , 5 ], as well as to reject bitter or new food items which may be extremely challenging for parents. Additionally, it was reported that repeated exposure to healthy foods (e.g., vegetables) along with limited access to unhealthy ones is a powerful factor that contributes to the development of healthier food preferences and dietary habits that may provide long term health outcomes [ 2 , 3 , 4 ]. Nonetheless, it emphasizes the need to offer children foods that are nutrient-dense and appropriate for them [ 2 , 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A healthy diet during infancy and toddlerhood is essential for healthy growth and development and fundamental for lifelong health (1,2). Parents are gatekeepers of their child's diet, both in relation to what is served, in what settings it is served and how it is served (3,4). Regarding what is served, a diet high in fruits and vegetables is highly recommended together with whole grains, milk and fish (5), however, national data show that it is challenging for parents to include vegetables and fish in their children's diet (6).…”
mentioning
confidence: 99%
“…2015; Walton et al . 2017; Daniels 2019). Parental concern about children’s fussy eating has recently been shown to be related to greater use of more controlling feeding practices (Harris et al .…”
Section: The Challenges Of Feeding Young Childrenmentioning
confidence: 99%
“…Coulthard & Harris 2003; Norman et al . 2015; Daniels 2019). Maternal anxiety may result from concerns around children’s diet and fussy eating but may also exacerbate the use of controlling and emotional feeding practices which are counterproductive ( e.g .…”
Section: Changes In Child Feeding Practices and Parents’ Anxiety Levelsmentioning
confidence: 99%